2014
DOI: 10.1002/hc.21202
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Thiophosphorylated Thioureas: Synthesis, Structure, and Cyclization Reaction

Abstract: A number of chiral racemic and enanthiopure thiophosphorylated thioureas were synthesized by the reaction of 2‐aminobutan‐1‐ol and 1‐(a‐aminobenzyl)‐2‐naphthol with O,O‐diethyl thiophosphoryl isothiocyanate. It was found that such thioureas undergo the cyclization reaction under basic conditions with hydrogen sulfide elimination and the formation of thiophosphorylated oxasines. X‐Ray single crystal diffraction revealed that the structure of thiourea is close to the prereaction state of the cyclization reaction. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Further, a number of chiral racemic and enanthiopure thiophosphorylated thioureas 58 synthesized by the reaction of 1-(α-aminobenzyl)-2-naphthol 1 with O , O -diethyl thiophosphoryl isothiocyanate 59 in dry benzene at room temperature for 24 h. It was found that such thioureas undergo the cyclization reaction under basic conditions with hydrogen sulfide elimination via two methods (method A: in dry acetone, triethylamine or 4-(dimethylamino)pyridine at room temperature for 7 days; method B: in chloroform and hexane, N , N ′-dicyclohexylcarbodiimide at reflux for 4 h) and afforded thiophosphorylated oxasines 60 as depicted in Scheme 19. 44…”
Section: Synthesis Of Naphthoxazinesmentioning
confidence: 99%
“…Further, a number of chiral racemic and enanthiopure thiophosphorylated thioureas 58 synthesized by the reaction of 1-(α-aminobenzyl)-2-naphthol 1 with O , O -diethyl thiophosphoryl isothiocyanate 59 in dry benzene at room temperature for 24 h. It was found that such thioureas undergo the cyclization reaction under basic conditions with hydrogen sulfide elimination via two methods (method A: in dry acetone, triethylamine or 4-(dimethylamino)pyridine at room temperature for 7 days; method B: in chloroform and hexane, N , N ′-dicyclohexylcarbodiimide at reflux for 4 h) and afforded thiophosphorylated oxasines 60 as depicted in Scheme 19. 44…”
Section: Synthesis Of Naphthoxazinesmentioning
confidence: 99%